A influência do pensamento político-pedagógico Freireano na práxis de educadores populares cearenses na década de 1960 - Souza, Maria das Dores Alves (2014)
The educative work integrated into the popular culture, the belief in man's ontological vocation of "being more" and the hope of social transformation led to the development of Freire's political and pedagogical ideas, which defends the critical view of reality and the participation of the oppressed as instruments of struggle to overcome the oppression suffered by the people in Brazilian society. As general objective, the research intends to understand the political and pedagogical contributions of Freire's thought in the praxis of popular educators of Ceará, in the 1960s It was based on a qualitative approach to privilege the meanings, experiences, feelings, attitudes and values of respondents. With the Historical Oral approach, semi-structured interviews were instruments to record the memories of teachers on professional practice. The subjects were five educators who have experienced popular education activities referenced in Freire. The theoretical basis directed to the understanding of the theoretical and methodological assumptions of Freire's thought, by referring mainly in the works of the author (1967, 1980, l987, 1994). The narratives demonstrate that praxis intertwine to dreams, hopes, desire for social justice and utopia to cause social, political and cultural changes, required by popular classes in the transitional context that Brazilian society in the 1960s was experiencing. The commitment of popular educators to develop practical literacy linked to the socioeconomic and cultural reality of the students was impressive. The pedagogical action, reading, writing and critical understanding of reality was worked as liberation instrument of exploitation and dehumanization conditions that students were experiencing in the context of Brazilian society in 1960s Thus, the praxis of popular educators contributed to raising the literacy level and the expansion of social and cultural organization processes of learners, making it a landmark in popular education of Ceará.